Resting-state functional connectivity in drug-naive pediatric patients with Tourette syndrome and obsessive-compulsive disorder. (October 2020) - Tikoo, Sankalp; Cardona, Francesco; Tommasin, Silvia; Giannì, Costanza; Conte, Giulia; Upadhyay, Neeraj; Mirabella, Giovanni; Suppa, Antonio; Pantano, Patrizia
Abstract: Previous studies in cohorts of Tourette syndrome (TS) or obsessive-compulsive disorder (OCD) patients have not clarified whether these two disorders represent two clinical conditions or they are distinct clinical phenotypes of a common disease spectrum. The study aimed to compare functional connectivity (FC) patterns in a pediatric drug-naive cohort of 16 TS patients without any comorbidity (TS), 14 TS patients with OCD (TS + OCD), and 10 pure OCD patients as well as 11 matched controls that underwent resting state fMRI. Via independent component analysis, we examined FC in the basal ganglia (BGN), sensorimotor (SMN), cerebellum (CBN), frontoparietal (FPN), default-mode (DMN), orbitofrontal (OBFN), and salience (SAN) networks among the above cohorts and their association with clinical measures. Compared to controls, TS and TS + OCD patients showed higher FC in the BGN, SMN, CBN and DMN and lower FC in the FPN and SAN. The TS and TS + OCD groups showed comparable FC in all networks. In contrast to controls, OCD patients exhibited increased FC in the BGN, SMN, CBN, DMN, FPN, and SAN. OCD patients also showed higher FC in CBN and FPN when compared with TS and TS + OCD patients both separately and as one group. Tic severity negatively correlated with FC in CBN and FPN in the TS group, while the compulsiveness scores positively correlated with the same two networks in OCD patients. Our findings suggest common FC changes in TS and TS + OCD patients. In contrast, OCD is characterized by a distinctive pattern of FC changes prominently involving the CBN and FPN.